2021
DOI: 10.3389/fchem.2021.767847
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Light-Triggered Bacterial Eradication Using a Nanowire Nanocomposite of Graphene Nanoribbons and Chitosan-Coated Silver Nanoparticles

Abstract: Bacterial infection is a major threat to human health. However, many antibacterial agents currently used are severely limited due to drug-resistance, and the development of side effects. Herein, we have developed a non-antibiotic nanocomposite consisting of chitosan (ChS) coated silver nanoparticles (AgNPs) and graphene nanoribbon (GNR)-based nanowires for light-triggered eradication of bacteria. The presence of AgNP/ChS significantly enhanced the interactions of the GNR nanowires with Pseudomonas aeruginosa, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…These AWHPMs possess potent antibacterial properties and biological affinities. [167,175,185,243] Amoxicillinincorporating multiwalled carbon nanotubes (MWCNTs) [30] and hollow mesoporous silica nanocapsules (HMSNs) [210] are two examples of such AWHPMs. Moreover, it should be noted that CTS compounds and hydrogels, synthesized with amine organics engaging in Schiff base reactions, possess innate bactericidal properties.…”
Section: Antibacterial Propertiesmentioning
confidence: 99%
“…These AWHPMs possess potent antibacterial properties and biological affinities. [167,175,185,243] Amoxicillinincorporating multiwalled carbon nanotubes (MWCNTs) [30] and hollow mesoporous silica nanocapsules (HMSNs) [210] are two examples of such AWHPMs. Moreover, it should be noted that CTS compounds and hydrogels, synthesized with amine organics engaging in Schiff base reactions, possess innate bactericidal properties.…”
Section: Antibacterial Propertiesmentioning
confidence: 99%
“…Adhesive, injectable, conductive, bio-compatible self-healing hydrogel N , O -carboxymethyl CS with incorporated AgNPs showing antibacterial activity against ATCC and clinical strains of E. coli , K. pneumonia , P. aeruginosa , S. aureus and MRSA as well as anti-biofilm activity against S. aureus , E. coli , and P. aeruginosa (ATCC strains) is suitable for the cure of infected wounds [ 206 ]. A strong bactericidal effect both in vitro and in vivo against MRSA was also observed with CS–Ag nanocomposites [ 207 ] and effective inhibition of MRSA and P. aeruginosa biofilms by CS–AgNPs with sizes 10–50 nm using a dose 100 μg/mL was reported by Vijayakumar et al [ 208 ] Nanocomposite of CS-coated AgNPs and nanowires based on graphene showed excellent near infrared (NIR) light-triggered photothermal eradication of P. aeruginosa biofilms and the inhibition of bacterial growth [ 209 ]. Nanocomposite films consisting of CS, and AgNPs, CuO NPs or TiO 2 NPs showed superb antibacterial activity against P. aeruginosa , E. coli , E. faecalis , Streptococcus sp., S. aureus and MRSA and were recommended as a dressing in the therapy of wounds [ 210 ].…”
Section: Applied Nanomaterialsmentioning
confidence: 99%